Analisis Upaya Guru dalam Mengatasi Kesulitan Belajar Membaca pada Siswa Kelas II SD Negeri 1 Patuktrejo Kecamatan Bonorowo Kabupaten Kebumen - Ulfa Ayu Rakhmawati; Henry Aditia Rigianti (Warta Pendidikan | e-Journal, 2022)
Reading difficulties are obstacles in reading which are indicated by the gap between their abilities and learning achievements. Difficulties in learning to read are often found in elementary school age children, as happened in the second grade of SD Negeri 1 Patukrejo. The purpose of this study was to find out what factors hindered students from learning to read in grade 2 SDN 1 Patukrejo and to find out how the teacher's efforts to overcome reading difficulties in grade 2 SDN 1 Patukrejo, Bonorowo District, Kebumen Regency. The research method used is qualitative research using descriptive methods. Data collection in this study was carried out using interview and documentation techniques. The subjects of this study were teachers and grade 2 students of SDN 1 Patukrejo. The results showed that (1) in grade 2 students of SDN 1 Patukrejo there were still some who still had difficulty reading, namely: (a) students had difficulty in distinguishing letters that were almost the same or similar in writing, students had difficulty reading word for word. , and (c) students have difficulty in omitting letters or words. (2) The main factors that cause students to have difficulty reading are: (a) lack of parental supervision (b) intellectual factors or intelligence and (c) friendship environment. (3) The teacher's efforts to overcome reading difficulties in grade 2 SDN 1 Patukrejo are: (a) using appropriate learning media, (b) providing additional tutoring, (c) providing homework, (d) providing learning motivation.